Effects of Adrenaline Containing Local Anesthesia on Blood Pressure and Blood Glucose Levels Undergoing Tooth Extractions – A Comparative Study: Adrenaline Effects during Tooth Extraction - Rehman, Ijaz ur; Zeb, Maham; Anwar, Malik Adeel; Khalid, Arsala; Tayyab, Tahmasub Faraz; Siddique, Kashif; Kushef, Hooria (Pakistan Journal of Health Sciences, 2024)
Exodontia, the most common dental procedure for damaged or decayed teeth, often utilizes local anesthesia with vasoconstrictors like adrenaline. Although effective, adrenaline can impact blood glucose levels and hemodynamic parameters, particularly in hypertensive and diabetic patients. Objectives: To compare changes in blood pressure and blood glucose levels among healthy, hypertensive and diabetic patients undergoing tooth extraction with adrenaline-containing local anesthesia. Methods: A total of 177 participants were split equally into three groups: healthy, hypertensive and diabetic. Prior to and twenty minutes’ post-injection, blood pressure, and blood glucose levels were measured while a local anesthetic containing 2% lignocaine HCL with 1: 100,000 adrenaline was administered. Sample paired t test and one-way ANOVA were employed in the analysis. Results: After the procedure, hypertensive patients experienced a significant decrease in random blood glucose levels (p=0.001). Similarly, systolic blood pressure exhibited a significant increase (p<0.001), while diastolic blood pressure significantly decreased (p=0.021), post-procedure.Diabetic patients showed a non-significant decrease in glucose levels (p=0.209) but a significant increase in both systolic (p<0.001) and diastolic blood pressure (p=0.002). Healthy patients experienced a significant increase in systolic blood pressure (p=0.015) but no significant changes in glucose levels (p=0.873) or diastolic pressure (p=0.301). Conclusions: Adrenaline in local anesthesia significantly increases systolic blood pressure in all patient groups, with pronounced effects in hypertensive and diabetic patients. Changes in blood glucose were significant only in hypertensive patients, while changes in diabetic patients were non-significant. These findings highlight the need for careful monitoring and personalized management strategies in dental procedures to minimize potential adverse effects and ensure patient safety.